2008
DOI: 10.1093/ecam/nen017
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine for Chronic Fatigue Syndrome

Abstract: More and more patients have been diagnosed as having chronic fatigue syndrome (CFS) in recent years. Western drug use for this syndrome is often associated with many side-effects and little clinical benefit. As an alternative medicine, traditional Chinese medicine (TCM) has provided some evidences based upon ancient texts and recent studies, not only to offer clinical benefit but also offer insights into their mechanisms of action. It has perceived advantages such as being natural, effective and safe to amelio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 40 publications
(35 reference statements)
0
57
0
1
Order By: Relevance
“…18 TCM methods for managing chronic fatigue have been widely adopted for the treatment of cancer and other conditions in China and elsewhere. [19][20][21][22][23][24] In oncology care, the TCM method most often used in China is a mixture of herbal compounds and decoction. McCulloch et al, 25 in a multilingual literature review and meta-analysis, reported that Astragalus mongholicus (huangqi)-based herbal medicine was associated with a trend (unconfirmed because of the quality of the study) of increased survival, tumor response, and performance status.…”
Section: Discussionmentioning
confidence: 99%
“…18 TCM methods for managing chronic fatigue have been widely adopted for the treatment of cancer and other conditions in China and elsewhere. [19][20][21][22][23][24] In oncology care, the TCM method most often used in China is a mixture of herbal compounds and decoction. McCulloch et al, 25 in a multilingual literature review and meta-analysis, reported that Astragalus mongholicus (huangqi)-based herbal medicine was associated with a trend (unconfirmed because of the quality of the study) of increased survival, tumor response, and performance status.…”
Section: Discussionmentioning
confidence: 99%
“…According to KM, UCF is categorized into patterns of deficiency or excess. UCF is mainly diagnosed the deficiency pattern, classified into qi, blood, yin, and yang deficiencies, and specialized treatments are then applied according to the particular deficiency patterns 10 . In general, PI diagnosis is a key tool of KM treatment and has great curative power for many chronic illness.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, UCF patients can be classified into deficiency syndrome or excess syndrome, which refers to the deficiency or excess in qi, blood, yin, and yang 10, 11. Previous studies mentioned that UCF is mainly considered to exhibit the deficiency pattern and therefore most patients are treated by invigorating qi and yang and nourishing blood and yin 10, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Placenta contains iron which replenishes the iron level in the body to eradicate fatigue and provides energy [27]. Human placenta are commonly used in traditional chinese medicine for the treatment of chronic fatigue syndrome [76]. A survey on 189 females on maternal placentophagy was investigated.…”
Section: Improves Health and Energymentioning
confidence: 99%